Healthcare utilization following spinal cord injury: Objective findings from a regional hospital registry. (4th March 2019) - Sikka, Seema; Callender, Librada; Driver, Simon; Bennett, Monica; Reynolds, Megan; Hamilton, Rita; Warren, Ann Marie; Petrey, Laura
Abstract : Objective: The purpose was to describe the prevalence and characteristics of healthcare utilization among individuals with spinal cord injury (SCI) from a Level I trauma center. Design: Retrospective data analysis utilizing a local acute trauma registry for initial hospitalization and merged with the Dallas-Fort Worth Hospital Council registry to obtain subsequent health care utilization in the first post-injury year. Setting: Dallas, TX, USA. Participants: Six hundred and sixty four patients were admitted with an acute traumatic SCI from January 2003 through June 2014 to a Level I trauma center. Fifty five patients that expired during initial hospitalization and 18 patients with unspecified SCI (defined by ICD-9 with no etiology or level of injury specified) were not included in the analysis, leaving a final sample of 591. Outcome Measures: Data included demographic and clinical characteristics, charges, and healthcare utilization. Results: Mean age was 46.1 years (±18.9 years), the majority of patients were male (74%), and Caucasian (58%). Of the 591 patients, 345 (58%) had additional inpatient or emergency healthcare utilization accounting for 769 additional visits (median of 3 visits per person). Of the 769 encounters, 534 (69%) were inpatient and 235 (31%) were emergency visits not resulting in an admission. The most prevalent ICD-9 codes listed were pressure ulcer, neurogenic bowel, neurogenic bladder, urinary tract infection, fluid electrolyte imbalance, hypertension, and tobacco use. Conclusion: Individuals with SCI experience high levels of healthcare utilization which are costly and may be preventable. Increasing our understanding of the prevalence and causes for healthcare utilization after acute SCI is important to target preventive strategies.